2019
DOI: 10.21278/brod70301
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an Optimal Fleet for a CNG Transportation Scenario in the Mediterranean Sea

Abstract: For the natural gas transportation, several technologies can be applied, having different effectiveness and costs depending on the analysed case. The Mediterranean Sea is presenting a typical scenario where compressed natural gas (CNG) transportation is particularly attractive compared to liquefied natural gas (LNG) and pipelines, not only for stranded gas shipping but also for transportations cases where CNG is usually representing the most economically convenient solution. Approaching the design of a CNG shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Thus, in Valencia (17), the last Mediterranean stop, a significant percentage of vehicles can be loaded. In Setubal (18) there is a substantial equilibrium of loaded and unloaded vehicles. Then, the ship is involved in the short portto-port [11] Portbury (19)-Cork (20)-Portbury (21).…”
Section: Transport Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in Valencia (17), the last Mediterranean stop, a significant percentage of vehicles can be loaded. In Setubal (18) there is a substantial equilibrium of loaded and unloaded vehicles. Then, the ship is involved in the short portto-port [11] Portbury (19)-Cork (20)-Portbury (21).…”
Section: Transport Scenariomentioning
confidence: 99%
“…A detailed explanation of all the modules of MDM (Figure 2) goes beyond the purpose of the present paper, which focuses only on stability issues. Nevertheless, more details can be found in previous literature, such as [3][4][5]13,[15][16][17][18]. Since the primary task of concept design is to find the ship size for required performance and payload as well as for the valuation of ship's total cost, it is usual practice to include most of the ship linear dimensions and main coefficients in the set of free design variables of the MDM.…”
Section: Mathematical Design Modelmentioning
confidence: 99%
“…As mentioned, the technologies used for the PV influence greatly the CNG ship design. Modern technologies combining composites and steel structures or using composite only, allow reducing the weight of the containment system, leading to more slender hull forms compared to first CNG ship prototypes [12]. Another distinctive characteristic of CNG units is the presence of a flat bottom part in the bow to allow the connection of the submerged turret loading (STL) for the gas loading operation [13].…”
Section: Cng Shipsmentioning
confidence: 99%
“…All the variables vary between a minimum and a maximum, as reported in Table 2. The ranges were selected based on of previous studies [11][12][13][14], where specific ranges of geometrical coefficients were identified for the development of other metamodels (e.g., seakeeping, station-keeping, propulsion and internal layout). To maintain compliance with the other models, the same ranges were applied for the common variables.…”
Section: Cng Ships Databasementioning
confidence: 99%
See 1 more Smart Citation